Penguatan Profil Pelajar Pancasila pada Siswa di SMP Negeri 4 Tomohon - Pangalila, Theodorus; Supit, Brain Fransisco (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The issues addressed in this community service activity encompass a range of social problems, including environmental challenges, national disintegration, and the rampant abuse of narcotics among youth, who are considered the future leaders of the nation. The emergence of these problems in Indonesia indicates a significant erosion of Pancasila values in societal, national, and state life. The specific problems identified are: (1) a lack of student understanding of the Pancasila Student Profile, (2) an increasing prevalence of intolerance within society, and (3) insufficient dissemination of the fundamental values of the Pancasila Student Profile among both teachers and students. The proposed solution in this activity is the implementation of socialization and training sessions to strengthen the Pancasila Student Profile. The outcomes of these activities clearly demonstrate an improved understanding of the Pancasila Student Profile among students.